Features of Adaptive Mechanisms in Children with Minor Cardiac Abnormalities - O.V. Okhapkina (Zaslavsky O.Yu., 2013)
The paper presents the features of adaptive-compensatory reactions in children with minor cardiac abnormalities (MCA) depending on the presence or absence of fibrillogenesis violations. It is proved that the most informative indicator of the progression of MCA regardless of the functional state of the connective tissue is a measure of aerobic capacity of the organism of the child.